Hubungan Pengetahuan Ibu Dengan Kunjungan Posyandu Pada Balita Di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu Tahun 2026 - Viola Dwi Nurul Fitriani; Desi Aulia Umami; Murwati Murwati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The infant mortality rate refers to the probability of a newborn dying before reaching the age of 5, expressed per 1,000 live births. In 2023, 4.8 million children under five died. In 2023, approximately 13,100 infant deaths occurred daily, a very high number of child deaths, most of which are preventable. The purpose of this study was to determine the relationship between maternal knowledge and Posyandu visits among toddlers in the Telaga Dewa Community Health Center (Puskesmas) work area in Bengkulu City in 2026. This study used a descriptive method with a cross-sectional approach. The sampling technique used proportional stratified random sampling, with a sample size of 89 toddlers in the Telaga Dewa Community Health Center (Puskesmas) work area in Bengkulu City. Univariate analysis results showed that the majority of respondents (57.3%) had sufficient knowledge and the majority (70.8%) actively attended Posyandu visits. The bivariate analysis yielded a p-value of 0.000 for the relationship between maternal knowledge and Posyandu visits for toddlers. It can be concluded that maternal knowledge is associated with Posyandu visits for toddlers in the Telaga Dewa Community Health Center (Puskesmas) work area of Bengkulu City in 2026. The results of this study are expected to encourage the Puskesmas to provide routine health education and monitor and remind mothers of toddlers about the Posyandu schedule to ensure more regular visits.